2004
DOI: 10.1016/j.pain.2004.01.030
|View full text |Cite
|
Sign up to set email alerts
|

5-HT receptors involved in opioid-activated descending inhibition of spinal withdrawal reflexes in the decerebrated rabbit

Abstract: The role of 5-HT(1B/1D), 5-HT(2) and 5-HT(3) receptors in mediating descending inhibition of spinal reflexes activated by application of fentanyl to the fourth ventricle has been studied in rabbits decerebrated under N(2)O/isoflurane anaesthesia. In the control state, intraventricular fentanyl (3-30 microg kg(-1)) depressed, to an equal extent, short- and long-latency reflexes in the medial gastrocnemius muscle nerve evoked by electrical stimulation of all sural nerve afferents. Inhibition of reflexes resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Seven families of 5‐HT receptors (5‐HT 1–7 ) have been identified, and all of them appear to present in the spinal cord (Millan, 2002). In previous studies, it has been reported that a variety of nonselective 5‐HT receptor antagonist have been shown to reduce the antinociceptive effects of systemic or supraspinal applied opioids (Liu et al , 2002; Nemmani and Mogil, 2003; Lo et al , 2004). In the present study, the finding that spinal selective blockade of 5‐HT 7 receptors by SB‐269970 completely inhibits the antinociceptive effect of systemic morphine suggests that an important contribution of the spinal 5‐HT 7 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Seven families of 5‐HT receptors (5‐HT 1–7 ) have been identified, and all of them appear to present in the spinal cord (Millan, 2002). In previous studies, it has been reported that a variety of nonselective 5‐HT receptor antagonist have been shown to reduce the antinociceptive effects of systemic or supraspinal applied opioids (Liu et al , 2002; Nemmani and Mogil, 2003; Lo et al , 2004). In the present study, the finding that spinal selective blockade of 5‐HT 7 receptors by SB‐269970 completely inhibits the antinociceptive effect of systemic morphine suggests that an important contribution of the spinal 5‐HT 7 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, laser-evoked nocifensive reflexes assessed with the presented stimulation paradigm may represent a promising yet unique assessment to evaluate nociceptive processing after human SCI. Such a technique may, for instance, be suitable to specifically investigate the involvement of A-delta fibers and C-fibers in clinical studies, e.g., targeting novel drug therapies or spinal maladaptive neuroplastic changes ( Clarke et al, 2002 ; Lo et al, 2004 ). To verify the assumption of inversely related spasticity and neuropathic pain, a further step would be to initiate targeted, ideally translational, research efforts to explicitly evaluate the excitation level of the nervous system and the structural lesion pattern of the spinal cord in the light of central neuropathic pain presentation.…”
Section: Discussionmentioning
confidence: 99%